1996
DOI: 10.1139/f95-253
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and diet of killer whales in northern Norway: seasonal patterns relative to the distribution and abundance of Norwegian spring-spawning herring

Abstract: Our objectives were to investigate the seasonal occurrence of photoidentified killer whale pods in relation to the distribution of Norwegian spring-spawning herring and whether or not pod-specific differences in the occurrence or diet of killer whales could be demonstrated. In a 4-year study, the killer whales occurred in different areas during the summer and the fall-winter, and these areas coincided with the distribution areas of herring. Killer whales were encountered most frequently during October-January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
78
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 7 publications
10
78
0
Order By: Relevance
“…A recent study on offshore-feeding killer whales (Orcinus orca) in this system found that they mainly targeted northeast Atlantic mackerel (Scomber scombrus) (Nøttestad et al, 2014b). This was in contrast to the earlier perception that their main prey was the Norwegian spring-spawning (NSS) herring (Clupea harengus) (Sigurjónsson et al, 1988;Similä et al, 1996;Simon et al, 2006). This has been the case at least for the more coastal areas, but no such focused large scale study prior to Nøttestad et al (2014b) had given attention to the offshore areas of this highly productive marine ecosystem.…”
Section: Introductionmentioning
confidence: 94%
“…A recent study on offshore-feeding killer whales (Orcinus orca) in this system found that they mainly targeted northeast Atlantic mackerel (Scomber scombrus) (Nøttestad et al, 2014b). This was in contrast to the earlier perception that their main prey was the Norwegian spring-spawning (NSS) herring (Clupea harengus) (Sigurjónsson et al, 1988;Similä et al, 1996;Simon et al, 2006). This has been the case at least for the more coastal areas, but no such focused large scale study prior to Nøttestad et al (2014b) had given attention to the offshore areas of this highly productive marine ecosystem.…”
Section: Introductionmentioning
confidence: 94%
“…Consistent with T. truncatus studies in the USA, similar movements out of study areas occur in winter, most likely in response to fluctuations in prey availability (e.g., Maze and Würsig, 1999;Fazioli et al, 2006;Speakman et al, 2010). Elsewhere, seasonal dolphin movement patterns are also typically linked to prey availability (e.g., Similä et al, 1996;Degrati et al, 2012Degrati et al, , 2013. In Bunbury, "potential dolphin prey" in the Leschenault Estuary, Koombana Bay, and near-shore coastal waters has been studied for seasonal abundance, biomass and calorific content (McCluskey et al, accepted).…”
Section: Environmental Factors Affecting Fluctuations In Seasonal Abumentioning
confidence: 99%
“…by killer whales Orcinus orca aggregating in the fjords hosting the population of NSS herring during autumn and early winter (Simila et al 1996). NSS herring have used these fjords for overwintering since the mid 1980 s (Holst et al 2002) and with the whales, tourism and whale-safaris have become more important for the region.…”
Section: Consumption and Ecological Consequences In The Oceanmentioning
confidence: 99%
“…The larvae drift northwards with the Norwegian Coastal Current and immature NSS herring spend the first 3-4 years in the Barents Sea. Adults, eggs and larvae of NSS herring are important food for many species at the coast (Durant et al 2003;Høines and Bergstad 1999;Simila et al 1996;Toresen 1991), and immature NSS herring are important prey in the Barents Sea (Bogstad et al 2000).…”
Section: Introductionmentioning
confidence: 99%